Evaluation of Strategic Plans in hardware companies in Cercado de Lima - Mejia- Rivera, Andrea; Urteaga-Ballena, Giovani; Méndez Gutiérrez, Leidy Lucia (LACCEI, 2024)
The study on strategic planning in hardware companies in Cercado de Lima in 2023 underscores the critical importance of proper strategy implementation. Linear regression analysis revealed that implementation has the most significant positive impact on the evaluation of strategic plans, with a standardized coefficient (Beta = 0.757) and high statistical significance (p-value = 0.000). This highlights that effective implementation is crucial for enhancing organizational performance. While strategy formulation and evaluation are also important, implementation emerged as the determining factor. Strategy evaluation, with a negative coefficient (-0.115), suggests the need for revising and optimizing these processes to maximize benefits. The findings indicate that a balanced approach to strategy formulation, implementation, and evaluation is essential for business success. In conclusion, hardware companies should focus their efforts on effective implementation and continuous, critical evaluation to adapt to changing market conditions and achieve sustainable growth